g-closed Sets in Ideal Topological Spaces
The notion of g-closed sets is introduced in ideal topological spaces. Characterizations and properties of I_g -closed sets and I_g -open sets are given. A characterization of normal spaces is given in terms of I_g -open sets. Also, it is established that an I_g -closed subset of an I-compact space is I-compact. , number=3 - D, journal=International Journal of Mathematics And its Applications, author=R. Asokan and O. Ravi and I. Rajasekaran and R. Sathiyapriya, year=2015, month=Nov., pages=31–41